Individual Career Guidance Approach for Science Subject Selection among Public Secondary School Students of Karagwe District, Tanzania - Josephat, Vaileth; Timothy, Dr. Mandila; Semali, Prof. Ladislaus M. (International Journal of Scientific Research and Management (IJSRM), 2024)
The study investigated how individual career guidance enhances the selection of science subjects among public secondary school students of Karagwe District. Anchored in Expectancy-Value Theory (EVT), the study employed a convergent design within the mixed methods approach. The study targeted 31 heads schools (HSs), 1225 students, and 31 teacher counselors (TCs) in 31 public secondary schools, and one District Education Officer (DSEO). The sample included 120 students, 10 TCs, 10 HSs, and 1 DSEO obtained through simple random, total population, and stratified random sampling techniques. Quantitative data were collected through questionnaires, while qualitative data were collected through interview guides and focus group discussion guides whose validity were made certain by research experts in the field of education. The reliability of .894 was established for students questionnaires based on the Likert-type items using Cronbach's Alpha technique while peer debriefing and triangulation methods were used for qualitative data. The quantitative data were descriptively analyzed with the aid of SPSS version 22 while qualitative data were subjected to a thematic analysis that involved familiarization, coding, topic generation, theme review, theme definition and name, and writing up. Ethical guidelines for research were conformed, which included obtaining approval for the study, seeking informed consent, maintaining confidentiality and anonymity, properly attributing sources, and acknowledging papers According to the study, students in Karagwe District have chosen science subjects differently as a result of receiving individualized career counseling. Students appreciate the significance of one-on-one career counseling sessions in helping them define their interests and aspirations in science subjects. The study revealed further that students can better align their goals and receive tailored support by receiving personalized advice and guidance on science subjects. The study came to the conclusion that individual career counseling is a useful tool since teacher counselors are crucial in helping students receive guidance that could boost their interest in and aspirations for science courses. According to the report, teacher counselors should receive more training so they may proactively identify students who are struggling or unsure about their future career prospects and offer them specialized counseling and support.